NEUTROSOFIK MODUL DAN SIFAT-SIFATNYA - ., Suryoto; Irawanto, Bambang; Puspita, Nikken Prima (MATEMATIKA, 2015)
Given any ring with unity and a commutative neutrosophic group under the additional operation, then from the both structures can be constructed a neutroshopic module by define the scalar multiplication between elements of the ring and elements of the commutative group. Further by generalized the neutrosophic module can be obtained a substructure of the neutrosophic module called a neutrosophic submodule. In this paper, from the concept of neutrosophic module and the ring with unity we study a generalization of classical module, that is a neutrosophic module and its properties. By utilizing the neutroshopic element as an indeterminate and an idempotent element under multiplication can be shown that most of the basic properties of clasiccal module generally still true on this neutrosophic struture.